2021
DOI: 10.1038/s41598-021-87899-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent ethanol promotes ventral subiculum hyperexcitability via increases in extrinsic basolateral amygdala input and local network activity

Abstract: The hippocampus, particularly its ventral domain, can promote negative affective states (i.e. stress and anxiety) that play an integral role in the development and persistence of alcohol use disorder (AUD). The ventral hippocampus (vHC) receives strong excitatory input from the basolateral amygdala (BLA) and the BLA-vHC projection bidirectionally modulates anxiety-like behaviors. However, no studies have examined the effects of chronic alcohol on the BLA-vHC circuit. In the present study, we used ex vivo elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Prior findings from our lab have identified profound sex differences in vHC synaptic adaptations promoted by chronic intermittent ethanol exposure (CIE), a rodent model of alcohol dependence. Although withdrawal from CIE was associated with increased anxiety‐like behaviour in both sexes, this adaptation was accompanied by vHC hyperexcitability in male rats and decreased vHC network excitability in females (Bach et al, 2021, 2021; Ewin et al, 2019). Additional studies will be needed to determine how these sexually dimorphic adaptations associated with chronic ethanol exposure relate to motivational (appetitive) aspects of drinking in male and female rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior findings from our lab have identified profound sex differences in vHC synaptic adaptations promoted by chronic intermittent ethanol exposure (CIE), a rodent model of alcohol dependence. Although withdrawal from CIE was associated with increased anxiety‐like behaviour in both sexes, this adaptation was accompanied by vHC hyperexcitability in male rats and decreased vHC network excitability in females (Bach et al, 2021, 2021; Ewin et al, 2019). Additional studies will be needed to determine how these sexually dimorphic adaptations associated with chronic ethanol exposure relate to motivational (appetitive) aspects of drinking in male and female rats.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for the frequent co-occurrence of these disorders is that their aetiology may involve maladaptive changes in common neural pathways. For example, many studies have reported that both AUD and PTSD are associated with dysregulated activity and connectivity in circuits that include the prefrontal cortex, amygdala and hippocampus (Almonte et al, 2017;Bloodgood et al, 2018;Santos et al, 2019;Skelly et al, 2017). Notably, recent studies have demonstrated that these brain regions are not homogenous structures but, rather, are comprised of distinct populations of cells with unique afferent and efferent connectivity that often encode behaviours with opposing valence (Beyeler et al, 2018;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Both the hippocampus and the BNST have been associated with alcohol use, with the BNST being specifically implicated in alcohol-related alterations to stress-processing ( Bach et al., 2021 ; Volkow et al., 2016 ). One recent small-scale study reported a greater number of streamlines between the hippocampus and the BNST in early abstinence women than in control women, a finding which was not seen in men ( Flook et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from both preclinical and human subjects have linked the hippocampus and the BNST to dispositional negativity and addictive behaviours ( Hur et al., 2018 ; Lebow and Chen, 2016 ; Mira et al., 2020 ; Shackman et al., 2016 ). Alcohol consumption in particular has been shown to alter stress processing via drug-induced changes to PVN projecting limbic regions, including alterations to BNST and subiculum receptor signalling ( Bach et al., 2021 ; Centanni et al., 2019 ; Haun et al., 2020 ; Mira et al., 2020 ). However, relationships between the microstructural properties of this putative subiculum-BNST pathway and dispositional negativity / alcohol use in humans are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from both preclinical and human subjects have linked the hippocampus and the BNST to dispositional negativity and addictive behaviours (Hur et al, 2018;Lebow & Chen, 2016;Mira et al, 2020;Shackman et al, 2016). Alcohol consumption in particular has been shown to alter stress processing via druginduced changes to PVN projecting limbic regions, including alterations to BNST and subiculum receptor signalling (Bach et al, 2021;Centanni et al, 2019;Haun et al, 2020;Mira et al, 2020). However, relationships between the microstructural properties of this putative subiculum-BNST pathway and dispositional negativity / alcohol use in humans are currently unknown.…”
Section: Subiculum -Bnst Connectivity In Humansmentioning
confidence: 99%